MORPHOLOGICAL CHARACTERISTICS OF THE RECURRENT ARTERY OF HEUBNER - Papazova, Marija; Zhivadinovik, Julija; Matveeva, Niki; Dodevski, Ace; Zafirova, Biljana; Trpkovska, Biljana; Ristic, Daniela (Journal of Morphological Sciences, 2018)
Cerebral circulation, especially arterial, in recent decades has attracted the interest of anatomists and clinicians. The aim of this study was to present the morphological and topographic characteristics of the Heubner artery. Anatomical characteristics of the recurrent artery of Heubner of 133 human brains without cerebrovascular pathology from both sexes at the age from 23 to 68 years were examined. Brain specimens were fixed in a 10% solution of formaldehyde, and the obtained material was analyzed using a stereoscopic light microscope. In 94% brain specimens had a recurrent artery of Heubner while in 6% of the brains we could not identify the artery. The artery was present as a single vessel in 76% of cases, and as a double vessel in 24% of cases. It originated from the junction of the anterior cerebral artery and the anterior communicating artery in 60% of the specimens, from the A 2  segment of the anterior cerebral artery in 21% of the specimens, and from the A 1  segment of the anterior cerebral artery in 19%. The length of the recurrent artery of Heubner ranged from 14 to 46 mm, with a mean value of 24 mm. The diameter of the artery ranged from 0.9 to 2.8 mm, with a mean value of 1.3 mm. Detailed anatomical knowledge of the recurrent artery of Heubner is important when considering vascular surgery in the area of the anterior portion of the circle of Willis.